Capacidad antioxidante y contenido de fenoles totales de plantas medicinales utilizadas tradicionalmente como antidiabéticas en la región Loreto - Arana Tello, Rosa Isis (2024)
The main objective of this study was to determine the antioxidant capacity and total phenol content of 50 medicinal plant species traditionally used as antidiabetic agents in the Loreto region. Antioxidant activity was evaluated by DPPH, ABTS and FRAP assays, and total phenol content was evaluated by Folin Ciocalteu method. The results showed that Euterpe oleracea was the species with the highest antioxidant capacity in all test. DPPH assays with a value of 5543.95 ± 178.32 µmol Trolox/g, ABTS with a value of 9775.27±5.08 µmol Trolox/g and FRAP with a value of 5725.12 ± 1.80 µmol Trolox/g. Likewise, Euterpe oleracea also presented the highest total phenol content with a value of 6376.02 ± 48.49 mg GAE/g, which evidenced a significant positive correlation between phenolic content and antioxidant capacity of the species studied. Petiveria alliacea and Urera baccifera were the species with the lowest antioxidant capacity and phenolic content. This finding highlights the importance of continuing research on the use of medicinal plants in the treatment of chronic degenerative diseases such as diabetes, since many of these species could serve as precursors of anti-diabetic nutraceutical products. The study also highlights the importance of considering factors such as the extraction method and solvent used, which influence the quantification of phenolic compounds and antioxidant activity. These results open the door to future research that can contribute to the development of pharmaceutical, food and agricultural products.